2003
DOI: 10.1021/es021026o
|View full text |Cite
|
Sign up to set email alerts
|

A Biomass-Supported Na2CO3 Sorbent for Flue Gas Desulfurization

Abstract: A novel sorbent for SO2 removal has been investigated. The sorbent is obtained by conventional incipient wetness impregnation of abandoned biomaterials (straw or dried leaves) with an aqueous solution of Na2CO3. A material with the composition 80 wt % Na2CO3/straw shows a desulfurization activity which is both higher and faster than that of the reference sample Na2CO3/gamma-Al2O3. The breakthrough and stoichiometric SO2 adsorption efficiencies for 80 wt % Na2CO3/straw reach 48.9% and 80.6%, respectively, at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Compared to fresh 45S5 samples, the aforementioned bands were obviously intensified and sharpened for the pellet aged for 30 days, implying a higher amount of Na 2 CO 3 . In addition, the two weak bands located at~1050 cm − 1 and~1665 cm − 1 corresponded to the deformation of gaseous CO 2 attached to C_O and solid Na 2 CO 3 , respectively [31,32]. The peak located between 1700…”
Section: Mechanism For Surface Pattern Formationmentioning
confidence: 97%
“…Compared to fresh 45S5 samples, the aforementioned bands were obviously intensified and sharpened for the pellet aged for 30 days, implying a higher amount of Na 2 CO 3 . In addition, the two weak bands located at~1050 cm − 1 and~1665 cm − 1 corresponded to the deformation of gaseous CO 2 attached to C_O and solid Na 2 CO 3 , respectively [31,32]. The peak located between 1700…”
Section: Mechanism For Surface Pattern Formationmentioning
confidence: 97%
“…Previous studies showed that these aqueous solutions work well in absorbing SO 2 in the flue gas [32,33]. Compared with CaO and ZnO suspensions, Na 2 CO 3 and Na 2 SO 3 solutions can avoid the clogging problem since they are clear liquids, and more cost-effective than ZnO ones.…”
Section: Pyrolysis Process Of the Znso 3 ·25h 2 O Samplementioning
confidence: 99%
“…Although natural materials and agricultural/industrial wastes are suitable adsorbents due to their low cost, availability and having such functional groups as hydroxyl, carboxyl and phenol, accurate prediction of the adsorption process is di cult due to the complexity of these materials and, hence, their use needs a thorough understanding of their chemistry and the processes affecting the bonds (Kietlinska & Renman, 2005;Oliveira et al, 2005). The main constituent of agricultural by-products is cellulose (C 6 H 10 O 5 ) n , which gains some negative charge and interacts with different water cations when lies under water; the main result of Colombic interactions is the high adsorption capacity of various cations on the adsorbents (Shang et al, 2003). Mokhrejee et al (2006) studied the phenol removal from aqueous environments by activated carbon (the strongest), biochar (the weakest) and sugarcane bagasse biochar, and showed that the removal e ciency was independent of the adsorbent type and the initial solution concentration; the e ciency increased with an increase in the adsorbent mass, reached a maximum value and then stopped increasing.…”
Section: Introductionmentioning
confidence: 99%